Analisis Keefektifan Bahasa Pemrograman C++ Sebagai Dasar Pembelajaran Untuk Mahasiswa Teknik Informatika - Akhmad, Syab Zaki (Universitas Pelita Bangsa, 2023)
Lately, the field of computer science has become increasingly popular among young people who wish to enter the academic world. Graduates from the computer science department are often rumored to become the most sought-after experts in the future. As students begin their academic journey, they will inevitably encounter various programming languages as tools for their studies. As an introduction, professors typically initiate the learning process with popular programming languages such as Java, Python, and C++. In this context, I will analyze various journals and provide answers as to why C++ can be considered an option for students who want to start learning programming.